Drastic Massive Loss of Women’s Diets Diversity Due to Changes in Season - Ngala, Sophie; Kaindi, Dasel (University of Nairobi, 2020)
A study was done in Mbooni Division, Makueni District, during two seasons, pre- harvest (n=73) and post-harvest (n=203). Non-lactating and non- pregnant women who had children aged between 2-5 years were the respondents concerning household dietary diversity in the two seasons. The diversity of women’s diets tends to decrease from 5 to 4 food groups during seasonal change. Even though the energy intake increased slightly after harvesting from an average of 2,039 Kilo Calories (kCal) to 2,097 kCal, the nutrient adequacy of the diet was unacceptable.
Keywords: Kenya; Nutrition